Pemetaan Nilpoten - Achmad Arifin (Journal of Mathematical and Fundamental Sciences, 1979)
Sari. Dibuktikan teorema mengenai dekomposisi pada ruang vector yang diakibatkan oleh suatu pementaan nilpotent. Dekomposisi ini, disamping ditentukan oleh indeks nilpoten, juga ditentukan oleh nolitas pemetaan. Abstract. The theorm on the decomposition of a vector space caused by a nilpotent map is proved. The decomposition is determined besides by the index of nilpotency, also by the nullity of the map.